2016
DOI: 10.5430/jnep.v6n5p111
|View full text |Cite
|
Sign up to set email alerts
|

A study on work engagement among nurses in Japan: the relationship to job-demands, job-resources, and nursing competence

Abstract: Objective: This study reviewed the state of work engagement among nurses in Japan, and the relationship to job demands and job resources. Additionally, our research attempted to clarify the role of work engagement on the effects that job-resources have on nursing competence.Methods: A questionnaire composed of the Utrecht Work-Engagement Scale the Brief Scales for Job Stress-Nurse and the Clinical Nursing Competence Self-Assessment Scale was distributed to 917 nurses working in hospitals in Japan.Results: A ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 22 publications
(26 reference statements)
2
6
0
Order By: Relevance
“…It means that simultaneously competence and self-efficacy contribute 74.9% in increasing work engagement, and the rest of 25.1% is influenced by other factors not examined. This result is in line with previous research from (Haruna & Mathandan, 2017;Hontake & Ariyoshi, 2017;Hu et al, 2021) bahwa kompetensi berpengaruh positif dan signifikan terhadap keterikatan kerja dan penelitian dari (Mache et al, 2014;Na-Nan, Khantong & Joungtrakul, 2021;Orgambized, Borrego & Aguado, 2019) states that self-efficacy has a positive and significant effect on work engagement. This situation reveals the theory's truth, which states that work engagement is a level where employees take sides with their work, participate actively, and consider that work is essential to them.…”
Section: The Effect Of Competence and Self-efficacy On Work Engagementsupporting
confidence: 90%
See 3 more Smart Citations
“…It means that simultaneously competence and self-efficacy contribute 74.9% in increasing work engagement, and the rest of 25.1% is influenced by other factors not examined. This result is in line with previous research from (Haruna & Mathandan, 2017;Hontake & Ariyoshi, 2017;Hu et al, 2021) bahwa kompetensi berpengaruh positif dan signifikan terhadap keterikatan kerja dan penelitian dari (Mache et al, 2014;Na-Nan, Khantong & Joungtrakul, 2021;Orgambized, Borrego & Aguado, 2019) states that self-efficacy has a positive and significant effect on work engagement. This situation reveals the theory's truth, which states that work engagement is a level where employees take sides with their work, participate actively, and consider that work is essential to them.…”
Section: The Effect Of Competence and Self-efficacy On Work Engagementsupporting
confidence: 90%
“…Level, generalization, and strength features are characteristics of self-efficacy. Selfconfidence allows them to act following what they believe to be a form of operational control (Haruna & Mathandan, 2017;Hontake & Ariyoshi, 2017;Hu et al, 2021). Furthermore, self-efficacy has a significant effect on work engagement (Mache et al, 2018;Na-Nan, Khantong & Joungtrakul, 2021;Orgambized, Borrego & Aguado, 2019), so it can be assumed that the research hypothesis: H1 : Simultaneously, competence and self-efficacy affect the work engagement of health workers in inpatient installations.…”
Section: The Effect Of Competence and Self-efficacy On Work Engagementmentioning
confidence: 99%
See 2 more Smart Citations
“…Internalized regulation is the most important type of motivational regulations that provide the real and valid driver for work achievement. [1,18,24] Essentially, happiness and recognition of influence on work are major psychological needs for supporting nursing workforce. Additionally, Scott in 2008 reported that happiness at work is a basic aspect of nurses' work satisfaction.…”
Section: In 2010 and Price In 2011mentioning
confidence: 99%